The Intention of Healthy Behavior during the COVID-19 Pandemic among Community Members in Indonesia: Applying the Theory of Planned Behavior - Heni Trisnowati; Helfi Agustin; Syafriani Syafriani; Yayi Suryo Prabandari (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: The Coronavirus-2019 (COVID-19) pandemic is a health emergency that has caused a humanitarian crisis in most countries worldwide. The steps to prevent and protect Indonesian community members from COVID-19 are by implementing “Gerakan Masyarakat Hidup Sehat“ or GERMAS (Healthy Living Community Movement). This study aimed to analyse the relationships between attitude, subjective norm, perceived control behavior, and intention to prevent COVID-19 transmission.Subjects and Method: This study used a cross-sectional design with convenient sampling. Data collection was conducted by an online survey and distributed by personal WhatsApp or WhatsApp groups between June 30-July 20, 2020. A total of 1,611 subjcts from 34 provinces in Indonesia were selected using consecutive sampling. The dependent variable was the intention to perform behavior that consist of bringing cutlery to work; smoking; exercising; consume vegetables, fruit and dring 8 glasses; cover the mouth when coughing; using a mask; using hand sanitizer; and washing hands with soap. The independent variable was perceived control, subjective norm, and attitude. The data analyzed using chi-square test.Results: Negative attitude (OR= 1.58; 95% CI= 1.16 to 2.20; p= 0.004), negative norms (OR= 2.28; 95% CI= 1.86 to 2.79; p<0.001), and perceived control is not supportive (OR= 2.08; 95% CI= 1.19 to 3.66) associated with perform healthy behavior among community members in Indonesia.Conclusion: Negative attitude, negative norms, and perceived control is not supportive were associated with perform healthy behavior and are statistically significant.Keywords: healthy behavior, intention, COVID-19, community, theory of planned behavior.Correspondence:Heni Trisnowati. Study Program of Public Health, Faculty of Health Science, Universitas Respati Yogyakarta (UNRIYO). JL. Raya Tajem KM 1.5 Maguwoharjo, Depok, Sleman, Yogyakarta, Indonesia 55282. Email: heni_trisnowati@respati.ac.id. Mobile: +628176362938.Journal of Health Promotion and Behavior (2022), 07(04): 341-355DOI: https://doi.org/10.26911/thejhpb.2022.07.04.07